Performance Evaluation of Selected Tannery Companies Enlisted in Dhaka Stock Exchange - Kiyoum, Enayat (Asian Accounting and Auditing Advancement, 2015)
Being a developing country Bangladesh has always been considered as having two natural comparative advantages over its competitors: the domestic livestock population and the low-cost available labor that can help transform this raw material into products suitable for export. The industry employs about 100,000 people directly, producing fine quality crust & finished leather for export as well as for home consumption. In this paper, I have tried to analyze the development and growth of Selected Tannery Companies Enlisted on the Dhaka Stock Exchange. It is observed that all the selected companies are able to experience stable growth in Total Sales, Total Assets, and Net Income during the period of 2007-2011. Sixteen trend equations have been tested for different activities of the Selected Tannery Companies. Among them, the trend value of Fixed Assets, Retained Earnings, Price Earning (P/E) Ratio, and Asset to Equity Ratio are positive in the case of all the selected Tannery Companies. The Square of the correlation coefficient (r2) has also been tested for all trend equations. The r2 of Total Assets, Total Sales, Inventory Turnover Ratio, Net Income, and Export Sales is more than 0.5, which indicates the prospect of selected Tannery Companies in Bangladesh is very bright.